Annex V: Monsoons - Cherchi, Annalisa (2021)
A monsoon refers to a seasonal transition of regimes in atmospheric circulation and precipitation in response to the annual cycle of solar insolation and the distribution of moist static energy (Wang and Ding, 2008; Wang et al., 2014; Biasutti et al., 2018). A global monsoon can be objectively identified based on precipitation contrasts in the solstice seasons to encompass all monsoon regions (Wang and Ding, 2008). In AR5, regional monsoon domains were identified starting from the definition of the global monsoon tailored over the continents and adjacent oceans, as in Kitoh et al. (2013). This Annex contains the definition of the global monsoon as used in AR6 (Section AV.2), it explains the rationale for the different definition of AR6 regional monsoons compared to AR5 (Section AV.3) and provides the definition and basic characteristics of each regional monsoon assessed (Section AV.4).